2007
DOI: 10.12681/bgsg.16326
|View full text |Cite
|
Sign up to set email alerts
|

Origin and Quality of Thermal Groundwaters in the Region of Farsala (E. Thessaly/Greece)

Abstract: Farsala Basin presents a remarkable geothermal interest. Areas exhibiting geothermal potential are directly related to faulted zones, represented mainly by cross-faulted systems of E-W, NW-SE and NNE-SSW direction. Thermal waters occur in the areas of Ampelia and Krini in boreholes of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 5 publications
0
4
0
6
Order By: Relevance
“…Even though in Ampelia area, no surface expression of geothermal system exists, the temperature values from the deep water boreholes (> 200 m depth) range from 20 to 41 o C. The Farsala Basin tectonic regime, combined with the existence of permeable and impermeable formations, create appropriate conditions for the development of an active geothermal system (Xatzis, 2001;Stamatis et al, 2007). The geothermal anomaly observed in the study area seems to be directly connected to the fractured zones by active fault system of the sub-basement formations.…”
Section: Discussion -Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though in Ampelia area, no surface expression of geothermal system exists, the temperature values from the deep water boreholes (> 200 m depth) range from 20 to 41 o C. The Farsala Basin tectonic regime, combined with the existence of permeable and impermeable formations, create appropriate conditions for the development of an active geothermal system (Xatzis, 2001;Stamatis et al, 2007). The geothermal anomaly observed in the study area seems to be directly connected to the fractured zones by active fault system of the sub-basement formations.…”
Section: Discussion -Conclusionmentioning
confidence: 99%
“…The morphology of the top of the basement is controlled by the neotectonic activity, expressed by large folds with axis direction NE-SW as well as by E-W and NW-SE striking faults (Spyridonos et al, 2002). Mariolakos et al (2001aMariolakos et al ( , 2001b and Stamatis et al (2007) describe the presence three different aquifers in the study area. One unconfined aquifer of important potentiality is developed in the unconsolidated deposits of the basin and suffers from overexploitation due to the supply of the irrigation needs of the area.…”
Section: Geological and Hydrological Settingmentioning
confidence: 92%
See 1 more Smart Citation
“…Generally, the study area but especially the southern part, which is formed by fault tectonics and is characterised by the presence of higher groundwater temperature in deep boreholes, is part of the broader area of East Sterea Hellas, where an increase in geothermal fluid is observed coinciding with the Pliocene-Quaternary volcanic activity resulted in the creation of the volcanic centers of Lichades in Evoikos Golf and of Mikrothives in northeastern Orthis mountain (Fytikas and Kolios 1979). In Farsala basin, which extends southern of the study area, geothermal reservoirs have been found in Krini and Ampelia regions with temperature up to 26.2 and 39.1°C respectively (Stamatis et al 2007).…”
Section: Groundwater Qualitymentioning
confidence: 92%
“…12.4 Γεωλογικά χαρακτηριστικά της περιοχής έρευνας και τα σημεία των γεωτρήσεων που εμφανίζουν θερμοκρασία >20,5 ο C και είναι οι πλησιέστερες στις γεωτρήσεις Β5 και Β13 που εντοπίζονται οι υψηλότερες τιμές θερμοκρασίας (Stamatis et al 2007).…”
Section: 22unclassified